2020
DOI: 10.1155/2020/1283080
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Outcomes following Pediatric Bone and Soft Tissue Sarcoma Surgery: A NSQIP Pediatrics Analysis

Abstract: Background. Pediatric bone and soft tissue sarcomas are rare; therefore, national registries are essential tools for orthopedic oncology research. Past studies provide excellent data on long-term prognosis and survival trends but fail to examine treatment-specific morbidity. The aim of this study is to use a national registry to describe patient demographics, comorbidities, and adverse events in the first thirty days following surgical management of pediatric bone and soft tissue sarcomas. Methods. A retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 38 publications
(54 reference statements)
2
18
0
Order By: Relevance
“…There is a role for database studies in pediatric orthopaedic surgery; however, it is important to consider these differences when interpreting study results, generalizing data to other populations, and selecting databases for future research. (14,16) 16 (15,17) 16.5 (15.5, 17) 0.06…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a role for database studies in pediatric orthopaedic surgery; however, it is important to consider these differences when interpreting study results, generalizing data to other populations, and selecting databases for future research. (14,16) 16 (15,17) 16.5 (15.5, 17) 0.06…”
Section: Discussionmentioning
confidence: 99%
“…The availability of data for pediatric patients is more limited since pediatric patients are often treated at specialized centers and commonly have public insurance 1,2. The most commonly used databases in pediatric orthopaedic research include the National Surgical Quality Improvement Program (NSQIP), the Healthcare Cost and Utilization Project (HCUP), and the Pediatric Health Information System (PHIS) 13–19. However, their patient populations and procedures for data collection and validation are distinct and slightly different 3,20…”
mentioning
confidence: 99%
“…The lack of ERAS-based protocols for pediatric cancer patients is an opportunity for improvement, considering the presence of surgical complications in this population. Gallaway et al found that 1 in 11 pediatric bone and soft tissue sarcoma surgical patients experienced complications within 30 days post-surgery, including wound dehiscence, surgical site infections, pneumonia, urinary tract infections, C. diff colitis, and unplanned readmissions related to the surgical procedure [ 10 ]. Additionally, 24% of patients in this study required blood transfusions due to excessive bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into this subject matter are lacking. Existing studies have relied upon national registries and claims databases 16–18 . While these sources allow for general implications, they lack the granularity necessary to parse out the nuances of readmission in this patient group 16–18 …”
Section: Introductionmentioning
confidence: 99%